A clinical case of severe Crimean hemorrhagic fever with prolonged persistence of the pathogen in combination with tick-borne borreliosis - K. V. Zhdanov; O. V. Mal’cev; K. V. Kozlov; P. I. Miklush; E. V. Peredel’skij; S. N. Sidorchuk; Yu. A. Kravchuk; A. S. Sigidaev; V. G. Dedkov; A. A. Konushkaliev (Журнал инфектологии)
Crimean haemorrhagic fever (Crimean-Congo haemorrhagic fever) – an important public health problem due to the wide geographical spread, the ability to cause epidemic outbreaks of disease and high mortality. Evidence that human infection in some cases may occur in direct contact with the patient (bypassing the vector) indicates a high risk of contamination of surrounding people. This article presents a case of severe Crimean haemorrhagic fever in combination with tick-borne borreliosis with different clinical manifestations of the disease with many complications developed due to both direct and indirect effects of virus not only on blood cells, the system of hemostasis and vascular component with the development of hemorrhagic syndrome, but also on many organs and systems of the body. The possibility of long-term persistence of the Crimean haemorrhagic fever virus in the human body against the background of the inhibition of the immune system of the body and the severe course of the disease associated with the development of life-threatening complications, leads to a high risk of death, prolonged restorative treatment and extended hospitalization.